2014
DOI: 10.1002/pola.27414
|View full text |Cite
|
Sign up to set email alerts
|

Rigid triol and diol with adamantane-like core derived from naturally occurringmyo-inositol and their polyaddition with diisocyanates

Abstract: Two orthoester derivatives 1 and 2 that are easily accessible from naturally occurring myo-inositol were exploited as new triol-and diol-type monomers bearing a rigid adamantane-like structure to polyaddition with diisocyanates that gave the corresponding networked and linear polyurethanes. DSC analysis of the networked polyurethanes revealed their high glass transition temperatures ranging from 155 to 248 C, suggesting the contribution of the rigidity of the adamantane-like structure introduced at the nodes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…Dichloromethane, triethylamine, and 1,4‐dioxane were purchased from Kishida Chemical Co., Ltd. and distilled over calcium hydride prior to use. myo ‐Inositol orthoester 1 (referred to as “triol 1 ” henceforth) was synthesized and purified according to a reported procedure …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dichloromethane, triethylamine, and 1,4‐dioxane were purchased from Kishida Chemical Co., Ltd. and distilled over calcium hydride prior to use. myo ‐Inositol orthoester 1 (referred to as “triol 1 ” henceforth) was synthesized and purified according to a reported procedure …”
Section: Methodsmentioning
confidence: 99%
“…Further, a myo ‐inositol orthoester can be easily synthesized under acidic conditions from myo ‐inositol and trimethylorthoacetate . The resulting orthoester 1 has an adamantane‐like core and three hydroxyl groups, making it a triol‐type monomer with a rigid core . Its polyaddition with diisocyanates yielded networked polyurethanes with higher T g than networked polyurethanes obtained by polyaddition of 1,3,5‐cyclohexanetriol (CHT) with diisocyanates, indicating the efficacy of incorporating the adamantane‐like rigid core into the crosslinking points for suppressing polymer chain mobility.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, myo ‐inositol can be produced from rice bran, which is often wasted because of its current lack of applications . So far, we and other research groups have demonstrated some efficient uses of myo ‐inositol as a starting material for the synthesis of polymers with repeating units bearing cyclic components. Examples include polyurethane synthesis based on the derivatization of myo ‐inositol into a rigid diol, 1 , and its polyaddition with diisocyanates (Scheme ) .…”
Section: Introductionmentioning
confidence: 99%
“…Our research interest has been focused on the utilization of myo ‐inositol, a naturally occurring cyclic hexaol, as a starting material for polymer synthesis . myo ‐Inositol and its derivatives can be found abundantly in various plants and animal organs.…”
Section: Introductionmentioning
confidence: 99%